ASUHAN KEBIDANAN PADA IBU HAMIL DENGAN HIPEREMESIS GRAVIDARUM DI KLINIK ROHUL SEHAT DESA RAMBAH - heny sepduwiana; Andriana (Fakultas Ilmu Kesehatan, 2021)
Pregnancy is a natural and physiological state. Nausea and vomiting experienced by pregnant women is a common thing because during pregnancy the HCG hormone will increase, if excessive nausea and vomiting will be a problem for pregnant women. in early pregnancy, has been reported to be associated with an increased risk for low birth weight, preterm delivery, small for gestational age, and perinatal death. The purpose of carrying out midwifery care for pregnant women Mrs. H is 36 years old with hyperemesis gravidarum at the Rohul Sehat Clinic, Rambah Village, thoroughly with a 7-step varney midwife mindset approach. Methods: Type of case study report using the 7-step Varney method, location of the Rohul Sehat Clinic, Rambah Village. The subject of the case study is a pregnant woman with hyperemesis gravidarum, Ny. H with H2P1A0 aged 36 years by providing care to pregnant women, case study time on August 24 to August 26, 2021. The data collection techniques include interviews and observations and secondary data includes documentation and literature studies. Results After the midwifery care for Mrs. H, 36 years old, H2P1A0 with hyperemesis gravidarum which took place gradually with midwifery care for mothers who experienced excessive nausea and vomiting, had been resolved. Conclusion It is hoped that the theory and practice of pregnant women with hyperemesis gravidarum will be developed further.